Optimization of Ultrasonic-Assisted Extraction of Protein from Jackfruit Seed Powder using Response Surface Methodology - srisuwan, warathaek; Chaiyawan, Kitti; Keawrattanakajorn , Pathchara (Srinakharinwirot University Engineering Journal, 2023)
This research aims to study the optimization of ultrasonic-assisted extraction of protein from jackfruit seed powder by response surface methodology (RSM). The effect of the ratio of enzyme to jackfruit seed powder, temperature and extraction time was investigated on protein removal. Box-Behnken Designs was used to determine the optimum extraction parameters. The result showed the optimum conditions were the ratio of enzyme to jackfruit seed powder 3.5 ml/10 g, temperature of 50 °C and extraction time about 15 minutes. The protein removal percentage was 64.42% at the optimum conditions. While, the jackfruit seed powder remained protein was 3.15%.